The Power of Nurse dalam Upaya Pemberdayaan Lansia untuk Peningkatan Ekonomi Melalui Program La-Market - Syamsidar, Syamsidar; Darmiati, Darmiati; Adelia Jasman, Mahfuda (Yayasan Mandar Indonesia, 2021)
One of the efforts in terms of empowering and optimizing the health and economic status of the elderly is in terms of exposing their merchandise to the public by presenting a marketplace among the elderly. Currently, internet technology is growing rapidly, it is felt that it is needed in various fields of business. Marketplace can be defined as an online application website that facilitates the buying and selling process from various stores, having more or less the same concept as traditional markets. Currently, we know that the increase in the number of elderly people is a very important issue and requires special attention, Indonesia from 2015 has entered the era of an aging population because the number of people aged 60 years and over exceeds 7%. Along with the increasing number of economic issues, it is difficult to access the economy at this time, especially during the pandemic, especially for the elderly. So that through this research, it is expected to be able to optimize the economy of the elderly as small business actors by accommodating various products and creativity of the elderly in marketing activities so that optimal trade occurs as an effort to help improve the welfare of the elderly through the marketplace. In this study, the researcher used the concurrent mixed method technique. This study took place in the Wonomulyo sub-district, Polewali Mandar district with a sample of about 10 productive elderly people. The results obtained from 10 productive elderly who were sampled as well as business actors concluded that with the economic role of the market place la market, it outlines the changes felt by the elderly, there are significant differences before and after using La Market as a sale that summarizes all elderly products which is the sample.